Effect of dietary incorporation of Spirulina platensis on the growth performance, carcass characteristics and meat quality in broilers - Venkateswarlu, S; Devasena , B; Sudheer , K (Journal of Meat Science, 2024)
This study was conducted to evaluate the effect of Spirulina platensis on growth performance, physiochemical properties of meat, carcass characteristics and breast meat quality in broilers. A total of 144-day old commercial broiler chicks were randomly divided into 3 dietary treatments with 4 replicates having 12 birds per replicate for a period 6 weeks. The dietary treatments were 0 (T1), 1(T2) and 2(T3) % spirulina inclusion in rations. Significantly (P
Keywords: Spirulina; Body weight gain; Psychrophiles; Crude protein; meat colour